TREE STRATIFICATION BASED ON ERUPTION DAMAGE LEVEL IN MOUNT MERAPI NATIONAL PARK YOGYAKARTA INDONESIA - Inggita Utami; Radhitiya Anjar Pramana Putra; Muhammad Saputra Wibowo; Febriant Isabella Yusuf; Fahmiatul Husna; Arviteno Eko; Dennis Susanto (Media Konservasi, 2021)
Mount Merapi’s eruption has caused damage to the forests in the Mount Merapi National Park (MMNP). Nine years after the eruption, the vertical structure of vegetation can illustrate the progress of succession. This study aimed to analyze the tree composition and stratification in different forest damage levels after the 2010 Merapi eruption. The study was conducted in March 2019 at three stations, namely station A (heavy damage area), station B (moderate damage area), and station C (minor damage area). Vegetation parameters in each station were taken in a 10x100 plot and were processed using a tree profile diagram. Abiotic parameters were measured in each plot and analyzed using the correlation test. The results showed that the three stations were still dominated by the tree in Stratum C, but the tree density and tree height varied in proportion to the damage level. Station A in the heavy damage area has the lowest tree density (23 trees/0.1 ha) with a maximum tree height of 12 meters, in contrast to Station C in the minor damage area with tree density reaching 195 trees/0.1 ha and maximum tree height reaching 30 meters. Nine years after the Mount Merapi big eruption, the MMNP forests in Yogyakarta Province are still classified as young secondary forests. Key words: diagram, profile, succession, structure, vertical